Preclinical usability study of multiple augmented reality concepts for K-wire placement - Fischer, Marius; Fuerst, Bernhard; Lee, Sing Chun; Fotouhi, Javad; Habert, Severine; Weidert, Simon; Euler, Ekkehard; Osgood, Greg; Navab, Nassir (International Journal of Computer Assisted Radiology and Surgery, 2016)
Purpose: In many orthopedic surgeries, there is a demand for correctly placing medical instruments (e.g., K-wire or drill) to perform bone fracture repairs. The main challenge is the mental alignment of X-ray images acquired using a C-arm, the medical instruments, and the patient, which dramatically increases in complexity during pelvic surgeries. Current solutions include the continuous acquisition of many intra-operative X-ray images from various views, which will result in high radiation exposure, long surgical durations, and significant effort and frustration for the surgical staff. This work conducts a preclinical usability study to test and evaluate mixed reality visualization techniques using intra-operative X-ray, optical, and RGBD imaging to augment the surgeon’s view to assist accurate placement of tools. Method: We design and perform a usability study to compare the performance of surgeons and their task load using three different mixed reality systems during K-wire placements. The three systems are interventional X-ray imaging, X-ray augmentation on 2D video, and 3D surface reconstruction augmented by digitally reconstructed radiographs and live tool visualization. Results: The evaluation criteria include duration, number of X-ray images acquired, placement accuracy, and the surgical task load, which are observed during 21 clinically relevant interventions performed by surgeons on phantoms. Finally, we test for statistically significant improvements and show that the mixed reality visualization leads to a significantly improved efficiency. Conclusion: The 3D visualization of patient, tool, and DRR shows clear advantages over the conventional X-ray imaging and provides intuitive feedback to place the medical tools correctly and efficiently.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Interventional imaging; Orthopedic and Trauma surgery; Usability study